Financial Performance Analysis of Companies in the Stock Exchange Istanbul Tourism Index - Tutar, Hasan; Ay, Gamze; Şahin, Mehmet (Journal of Tourism, Sustainability and Well-being, 2025)
This study aimed to evaluate the financial performance of tourism companies listed on the Borsa Istanbul Stock Exchange (BIST) using a multi-criteria decision-making method called the Range of Values (ROV) technique. This approach was chosen because it allows multiple financial indicators to be considered simultaneously, thus providing a more holistic assessment than single-metric evaluations. The researchers selected eight financial ratios, spanning liquidity, leverage, profitability, and activity measures, as evaluation criteria. These ratios were applied to assess the financial performance of the nine tourism companies traded on BIST from 2015 to 2021. The results of the ROV analysis revealed that the financial leverage ratio is the most critical indicator in determining the overall financial performance of tourism firms. This suggests that a company's capital structure and debt management are crucial to its financial standing within the tourism industry. By ranking the nine companies based on their aggregated financial performance scores, this study provides insights into their relative financial health. This information can be valuable for investors, creditors, and industry analysts when making informed decisions regarding the tourism sector. The findings of this study demonstrate the utility of multi-criteria decision-making methods, such as the ROV technique, in comprehensively evaluating companies’ financial performance. The authors conclude that financial ratios can be effectively employed to assess the performance of tourism companies, and that the ROV approach offers a robust framework for such assessments. This study contributes to the literature by providing a nuanced understanding of the financial drivers of performance in the tourism industry, which can inform strategic decision-making and resource allocation within the sector.